IMPLEMENTATION OF A REAL-TIME IoT-BASED MONITORING ANDADAPTIVE LOAD CONTROL SYSTEM FOR SMALL-SCALE SOLAR ENERGYINSTALLATIONS (Universal International Scientific Journal, 2026)
This article discusses the development and implementation of a real-time monitoring and adaptive load control system based on IoT technologies for small-scale solar power systems. The proposed system is built on the ESP32 microcontroller and allows continuous measurement of key parameters such as voltage, current, power, temperature, and light intensity. The obtained data is transmitted to a remote server via Wi-Fi and analyzed through a user interface. The adaptive control algorithm optimizes the load in accordance with changes in external environmental conditions and reduces energy losses. Experimental results have shown that the system is of practical importance in increasing energy efficiency and ensuring stable operation of small-scale solar power systems.
Keywords: Solar energy; IoT monitoring; adaptive control